THE EFFECTIVENESS OF ALCOHOLIC BEVERAGE DISTRIBUTION CONTROL THROUGH BULELENG REGENCY REGULATION NO. 9 OF 2016 - Premasanti, Nyoman Asri; Mahendrawati, Ni Luh Made; Styawati, Ni Komang Arini (jfpublisher, 2025)
The circulation and sale of alcoholic beverages in Buleleng Regency remain prone to violations, particularly regarding business licensing and permitted trading locations. Despite existing regulations, supervision is often ineffective, allowing unauthorized sales and non-compliant business operations. Challenges in enforcement contribute to ongoing violations. This study aims to evaluate the effectiveness of supervision over the circulation and sale of alcoholic beverages in Buleleng Regency and identify key obstacles hindering proper enforcement. This research uses an empirical legal method to examine the gap between law and social reality through juridical and sociological approaches, supported by qualitative analysis of observations, interviews, and documentation linked to legal theories and regulations. The supervision of alcoholic beverage sales in Buleleng Regency is carried out through guidance, field inspections, and enforcement by an Integrated Team of various technical agencies. However, this supervision has not been fully effective, as the goals outlined in the regulations have not been achieved. Many businesses still operate without licenses and violate location restrictions. Several factors hinder effective implementation, including weak enforcement, overlapping responsibilities among agencies, low legal awareness among business owners, and limited public understanding of the health and social impacts of alcohol consumption.